Methodology for the posdegree curricular management in statistics for the Health Information System university graduate - Bolivar Alejandro Pérez Rodríguez; Isabel Alonso Berenguer; Antonio Salgado Castillo; Alexander Gorina Sánchez; Eduardo López Hung (Centro Provincial de Información de Ciencias Médicas, 2017)
Taking into account the necessity and importance of the posdegree training of Health Information System university graduates, a methodology aimed at favoring the design of the diverse modalities of this type of training was elaborated, to perfect the statistical education of these professionals and promote their working performance. This methodology takes into consideration the statistical requirements of their jobs and the inadequacies that they show in the use of methods and similar techniques.